Escaping the cell: virtual reality escape rooms in biology education - Christopoulos Athanasios; Mystakidis Stylianos; Cachafeiro Enrique; Laakso Mikko-Jussi (TAYLOR & FRANCIS LTD, 2022)
Individuals’ conceptual knowledge of contemporary biological issues influences ethical attitudes and life decisions around health, as evidenced by the recent worldwide debate on vaccinations. The reasons for which the public opinion is so critically divided can be partially explained from the didactic approaches used in biology education. In view of the rapid evolution of Virtual Reality (VR) as well as the increasing interest that youths have shown toward Escape Rooms (ER), an unexplored research and development avenue is identified. In this experimental study, we present the design and development steps as well as the evaluation of a VRER dedicated to biology education. For comparison purposes, an educational instructional video utilising the storytelling technique was also prepared. Both approaches were examined in the upper secondary education context with participants (N = 50) emerging from the Applied Sciences academic path. The key-findings suggest that the active learning approach leads to increased knowledge acquisition, in the short term, as opposed to the passive learning approach but no significant differences were identified in the long term (knowledge retention) across the methods. Based on the instructional decisions made and the key-findings emerged we provide implications and guidelines for the design, development, and integration of VRER in education.